Accuracy of the Edinburgh Postnatal Depression Scale (EPDS) for screening to detect major depression among pregnant and postpartum women: systematic review and meta-analysis of individual participant data - Levis, B; Negeri, Z; Ying, S; Andrea, B; Thombs, BD; Stein, A; DEPRESsion Screening Data (DEPRESSD) EPDS Group (BMJ Publishing Group, 2020)
Objective: To evaluate the Edinburgh Postnatal Depression Scale (EPDS) for screening to detect major depression in pregnancy and postpartum.